Critical Review on Naga Formulations in Rasayogasagar - Yadav, Shobhnath (International Journal of Pharmaceutical & Biological Archive, 2016)
Introduction-Ancient medicine recognizes the importance of metals in treating different mitigation of disease. â€œBhasmaâ€ (metallic preparations in calx form) are prepared by incineration of metal by various processing techniques described in Ayurvedic literature. These metallic preparations occupy a significant place in Ayurvedic pharmacopoeia in Part-1, Volume -VII .The wellâ€‘known metallic bhasma frequently used in Ayurveda include PÄrada (mercury), Svará¹‡a (gold), Rajata(silver), TÄmra (copper), Loha (iron), NÄga (lead) and Vaá¹…ga (tin). Beacause Bhasma is considered highly effective and potent.Ayurvedic classics also quote significant information about administration of Naga Bhasma (metallic preparations in calx form). Naga Kalpas are the unique compound herbo-mineral formulations where Naga is used as a major and minor ingredient and most of the Naga (lead) formulation was compiled in Rasayogasagar.These formulation has been taken from original references books.Till date no work has been found published on different percentage of Naga in Naga kalpa of Rasayogasagar. Taking in to consideration that it has been decided to calculate percentage of Naga Bhasma, anupan, dose, therapeutic indications in different formulations of Rasayogasagar.Aim-The present work aims to collect information on various formulations of NÄga bhasma mainly indicated in treating Prameha (Diabeties, Kamala (Jaundice) , Kustha (Skin disease) etc. and to elaborate the safety and efficacy of NÄga bhasma in various formulation.Materials and Methods: Critical review of formulations of NÄga bhasma is compiled from Rasayogasagar. Ayurvedic texts and the therapeutic efficacy of NÄga bhasma is discussed on the basis of available data.Results and Conclusion: Antidiabetic formulations of NÄga bhasma were discovered around 12th century CE. There are 231 formulations of Rasayogasagar contain NÄga bhasma and in which 50 formuulation mainly indicated for Prameha. HaridrÄ (Curcumalonga Linn), Ä€malakÄ« (Emblica officinalis), Guá¸Å«ci (Tinosporacordifolia) and Madhu (honey) enhance the antidiabetic action of NÄga bhasma and also help to prevent diabetic complications as well as any untoward effects of NÄga bhasma. On the basis of there viewed research, it is concluded that NÄga bhasma possesses significant antidiabetic property.